MARKETING COMMUNICATION STRATEGY IN INCREASING SALES PROPERTY IN PESONA PURNAMA HANDIL BAKTI RESIDENTIAL COMPLEX - M. Agus Humaidi; Rico Rico; Junaidy Junaidy (Jurnal Ekonomi, 2022)
Marketing Communication Strategy for a product in a company is a form of marketing improvement strategy in advancing a company and making the products offered to be more attractive. The type of research used is qualitative research with a descriptive approach. The data sources used in this study are primary data sources and secondary data sources with a total of 5 informants. Data collection techniques using observation, interviews and documentation. The results of the study show that the Marketing Communication Strategy in Increasing Property Sales in the Pesona Purnama Handil Bakti Housing Complex is fairly good with reference to indicators (1) Advertising (Advertising), where the form of communication of marketing staff is personally able to convey and explain sales products to Users clearly and easy to understand. Then in indicator (2) Sales promotion, via Whatsapp, making it easier for customers and marketing staff to exchange information. Indicator (3) Public Relations, which now tends to make more use of social media in finding customers and following up product explanations to consumers. Indicators (4) Personal Selling, where in marketing they carry out good promotions in fast and easy-to-understand language and Indicators (5) Direct Sales, also always use social media, carry out promotions by giving away products for free when there is a promo, determine a strategic location for customers. Then the supporting factor is consistency in the utilization of digital developments while the inhibiting factor is the lack of cooperation.